Pengaruh Sikap Karyawan Terhadap Komitmen Organisasi - Rd. Okky Satria; Anton Tirta Komara; Boy Suzanto (Majalah Bisnis & IPTEK, 2018)
This study aims to determine the effect of employee attitudes component sconsisting of affective, cognitive and behavioral of employees towards organizational commitment. Hypothetical testing was used by sample tested employees in one of the Tax Service Office in Bandung with 95 employees for samples. Sampling techniques used simple random sampling of existing populations. Data analysis techniques were using path analysis. This research method is included in the survey method category. The results of the study prove that there is an influence of attitudes towards employee commitment of 72.2% while the remaining 27.8% is influenced by other factors that are not examined in this study.